Effects of Glutamate on Growth Performance, Gut Digestion and Antioxidant Capacity in Juvenile Little Yellow Croaker - Ruining Liu; Yu Zhang; Xiao Liang; Bao Lou; Junquan Zhu (Fishes)
This study is to explore the alleviating effects of glutamate on intestinal damage in cultured little yellow croaker. A total of 900 juvenile fish at a weight of 30.68 ± 0.12 g were randomly separated into six groups with three replicates each, and were fed a basic diet (protein at 44.42% and lipid at 12.48%) with additional glutamate at 0.00%, 0.40%, 0.80%, 1.2%, 1.60%, and 2.00%. Each replica group consisted of 50 fish in a breeding barrel (radius 1.0 m, height 1.5 m), and the experiment lasted for 54 days. The results showed that supplementation with 0.4–1.2% glutamate significantly improved the survival rate, which increased from 75.56% to 91.11%, reduced the feed conversion rate from 1.75 to 1.57, and increased the protein efficiency ratio from 1.55 to 1.85 (p < 0.05). In the intestines, the addition of 0.40–1.2% glutamate increased muscle thickness and villus height (p < 0.05), as well as the activities of pepsin, trypsin, α-amylase, and lipase (p < 0.05). Enzyme activity analysis indicated that the addition of 0.4–1.2% glutamate in the feed significantly enhanced the activities of serum Total Superoxide Dismutase (T-SOD), catalase (CAT), and glutathione peroxidase (GPx) antioxidant enzymes (p < 0.05). Transcriptome analysis of the 1.2% and 0% groups revealed that differentially expressed genes were enriched in glutathione synthesis, nutrient absorption and metabolism, and viral protein interaction with cytokine and cytokine receptor pathways. qPCR experiments verified that the addition of 1.2% glutamate significantly up-regulated the expression of antioxidant-related genes, including glutathione synthetase and Nrf2. In conclusion, the addition of glutamate can enhance growth performance, increase intestinal digestive capacity, activate intestinal glutathione synthesis to alleviate intestinal damage, and maintain intestinal health.